An extension of Wirtinger’s inequality to the complex integral - DRAGOMIR, Silvestru Sever (Studia Universitatis Babeș-Bolyai Mathematica, 2023)
In this paper, we establish a natural extension of the Wirtinger inequality to the case of complex integral of analytic functions. Applications related to the trapezoid inequalities are also provided. Examples for logarithmic and exponential complex functions are given as well. Mathematics Subject Classification (2010): 26D15, 26D10.